The Effect of Educational Game Use on Mathematics Learning Outcomes of Seventh-Grade Students at UPT SMP Negeri 5 Panca Rijang - Agustan Agustan; Usman M; Madaling Madaling; Muhammad Takdir (Universitas Muhammadiyah Enrekang, 2025)
This study aims to examine the effect of using educational games on the mathematics learning outcomes of seventh-grade students at UPT SMP Negeri 5 Panca Rijang. The background of this research is rooted in the importance of utilizing interactive instructional media to enhance students' interest and understanding of learning materials, particularly in mathematics. The research employed a true experimental design involving two groups: an experimental class that used educational games and a control class that used printed learning materials. Data were collected through post-tests and analyzed using descriptive and inferential statistics (t-test) with the assistance of SPSS version 27. The results revealed that the average score of the experimental class was 81.17, which was significantly higher than the control class, which had an average score of 60.00. The hypothesis test showed a significance value (2-tailed) of 0.000 < 0.025, indicating a significant effect of using educational games on students’ mathematics learning outcomes. These findings suggest that educational games positively influence students’ academic achievement in mathematics. Therefore, the integration of educational games into the learning process is recommended to foster a more interactive and engaging learning environment